Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

(7x+1)(2x−3)=0 solve for roots​

Sagot :

Answer:

x = - [tex]\frac{1}{7}[/tex], x = [tex]\frac{3}{2}[/tex]

Step-by-step explanation:

Given

(7x + 1)(2x - 3) = 0 ← in standard zero product form

Equate each factor to zero and solve for x

7x + 1 = 0 ⇒ 7x = - 1 ⇒ x = - [tex]\frac{1}{7}[/tex]

2x - 3 = 0 ⇒ 2x = 3 ⇒ x = [tex]\frac{3}{2}[/tex]

Answer:

x = - 1 / 7   and x = 3 / 2

Step-by-step explanation:

14x2 - 21 x + 2x- 3 = 0

14x2  - 19x -3 = 0

x = 1 9 + 23 / 28 = 3 / 2

x = 19 - 23 / 28 = - 1 / 7

7x + 1 = 0 ⇒ 7x = - 1 = -1 / 7

2x - 3 = 0 ⇒ 2x = 3 = 2/ 3

Hope this answer helps you :)

Have a great day

Mark brainliest